Lunasin alleviates pulmonary inflammation in A549 alveolar epithelial cells and C57BL6/J mice in obese-mimicking conditions - Chang, Wan-Sheng; Huang, Pei-Ying; Hsieh, Chia-Chien (Frontiers in Nutrition, 2026)
BackgroundObesity is accompanied by low-grade and chronic pathological development that can worsen pulmonary inflammation and fibrosis. This study investigated the potential of lunasin, a naturally occurring seed peptide with multiple bioactive properties, to attenuate lung inflammation in A549 pulmonary epithelial cells and in C57BL6/J mice fed with the high-fat diet.MethodsIn vitro, palmitic acid (PA) and lipopolysaccharide (LPS) were used to mimic an obese inflammatory microenvironment. The cultured supernatants were collected for cytokine analysis and cells were collected for specific protein analysis. In vivo, mice were fed a high-fat (HF) diet or an HF diet supplemented with lunasin-enriched soy protein isolated (HFL) from 6 until 22 weeks of age. The lung and spleen samples were collected for future analysis.ResultsLunasin inhibited PA- or LPS-induced interleukin (IL)-6, monocyte chemoattractant protein (MCP)-1, and transforming growth factor (TGF)-β secretion. While LPS reduced surfactant protein D (SP-D) expression, lunasin restored SP-D by inhibiting the nuclear factor kappa B (NF-κB) signaling pathway. Additionally, pulmonary fibrosis was induced by TGF-β-induced epithelial-mesenchymal transition (EMT), as indicated by reduced vimentin and preserved E-cadherin expression. However, lunasin did not affect the TGF-β-induced EMT marker in A549 cells. In vivo, HFL-fed mice exhibited lower tumor necrosis factor (TNF)-α and TGF-β levels in lung homogenate compared with HF-fed controls. Lunasin supplementation also enhanced the secretion of T helper cell type 1 (Th1) cytokines, including IL-2 and interferon (IFN)-γ, increased the Th1 (IL-2)/Th2 (IL-4) ratio, and reduced the IL-17A level in splenocytes.ConclusionIn summary, in vitro, lunasin attenuated pro-inflammatory cytokines, possibly through enhancing SP-D expression and inhibiting NF-κB signaling in A549 cells. In vivo, dietary lunasin supplementation reduced pulmonary inflammation and modulated splenic cytokine balance. This study reveals for the first time that lunasin is a promising candidate for mitigating obesity-related pulmonary inflammation.